SMART PARKING COMMUNITY SUPPORTS PARKING VEHICLE - Dr. S.Gopinath; G.Kowsalya; S.Arularasi; R Pradeepa; R Mekala (International Journal of Innovations in Engineering Research and Technology, 2023)
Cooperation between vehicles facilitates traffic management, road safety and infotainment applications.However, cooperation requires trust in the authenticity of the information received. In this paper, we address the challenge of securely exchanging information about parking availability. Trust is important in assisting in deciding whether interrogation is appropriaterely on information received about free parking spaces near your destination and thus ignore other possible spaces on the route.Therefore, we propose Parking Communities, which provide a distributed and dynamic way to set up Vehicle groups help each other find safe parking spaces in their respective community areas.Our approach is based on modern, high-performance encryption and signature algorithms as well as a well-understood mathematical trust assessment model. This approach enables end-to-end encrypted request-response communications combined with geolocation and can be used as an overlay to existing vehicular network technologies. We provide comprehensive comparisons with other security solutions The architecture and simulation results demonstrate the feasibility of our method.